Methodological approaches to estimation of teenagers' health - Shudro S.A. (Medičnì Perspektivi)
On the basis of International classification of functioning, limitations of vital activity and health, model of estimation of teenagers' health considering these changes from positions of functioning of the organism and context factors was developed. According to this model five groups of health of school-children of secondary schools were distinguished. Teenagers with sufficient level of structure and function of organism, structure of personality and mental functions, activity and participation in general educational processes compose group I A. Teenagers with sufficient level of structure and function of organism, mental functions and disorders of structure of personality, activity and participation in social life compose group I B. Teena¬gers with sufficient level of structure of the organism and personality, activity and participation in social life, disorders of organism functions and psychic functions compose group II. III A group - teenagers with disorders of structure of the organism and personality, functions of the organism and sufficient mental functions, participation in the social life. III B group - teenagers with disorders of structure and functions of the organism, structure of personality and psychic functions, low level of activity and participation in social life. The model, advanced methods and the software made it possible to create information technology of estimation of teenagers' health; this raises quality of diagnostics by 20,3%.